2020
DOI: 10.1038/s41467-020-18318-7
|View full text |Cite
|
Sign up to set email alerts
|

India’s potential for integrating solar and on- and offshore wind power into its energy system

Abstract: This paper considers options for a future Indian power economy in which renewables, wind and solar, could meet 80% of anticipated 2040 power demand supplanting the country’s current reliance on coal. Using a cost optimization model, here we show that renewables could provide a source of power cheaper or at least competitive with what could be supplied using fossil-based alternatives. The ancillary advantage would be a significant reduction in India’s future power sector related emissions of CO2. Using a model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(42 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…Sixth, the information contained in the assessment along with supply cost curves is a measurable step forward and fills in a significant information gap that is present in current integrated assessment models where solar PV potentials are often represented as aggregated potentials for utility and rooftop installations. Our assessment provides insightful findings and technical potential datasets that will certainly aid in accurately modeling the future carbon-neutral scenarios to inform national energy policies [61][62][63][64][65][66] . This will no doubt aid in exploring sustainable and inclusive low-carbon future possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Sixth, the information contained in the assessment along with supply cost curves is a measurable step forward and fills in a significant information gap that is present in current integrated assessment models where solar PV potentials are often represented as aggregated potentials for utility and rooftop installations. Our assessment provides insightful findings and technical potential datasets that will certainly aid in accurately modeling the future carbon-neutral scenarios to inform national energy policies [61][62][63][64][65][66] . This will no doubt aid in exploring sustainable and inclusive low-carbon future possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Low‐carbon energy 1,2 involves many fields, and different fields have different data types and visualization methods. This chapter mainly analyzes the three representative fields of Smart Grid, Electrical Vehicle, and Green Building.…”
Section: Data Visualization In Low‐carbon Energy Related Areasmentioning
confidence: 99%
“…Authors concluded that India could satisfy 80% of the expected demand in 2040 with wind and solar energy, and lower costs. Still, coal plays a significant role as a backup capacity, balancing the power system throughout a year [21]. Gulagi et al (2017) explored 100% renewable energy transition pathways for India until 2050 using a set of alternative energy storage, generation, and few demand-side technologies to balance demand and supply.…”
Section: Introductionmentioning
confidence: 99%